PENGARUH BUDAYA KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CABANG WINDU KARSA BAKAUHENI LAMPUNG SELATAN - Herwanto Herwanto; Egi Radiansyah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research is a survey research. The population used in this study were all employees at PT. Windu Karsa Bakauheni Branch, South Lampung. The object of this research is all employees at PT. Windu Karsa Bakauheni Branch, South Lampung. The analysis technique used is multiple regression analysis. The conclusions of this study are 1) Work Culture Has a Significant Influence on Employee Performance. 2) Work Discipline Has Significant Effect on Employee Performance. 3) Variables of Work Culture and Work Discipline Have a Significant Influence on Employee Performance at PT. Windu Karsa Bakauheni Branch, South Lampung.